Jobless Growth? Okun's Law in East Asia - Hanusch, Marek (World Bank, Washington, DC, 2012)
Was economic growth in East Asia jobless? This paper addresses this question using data from eight East Asian countries during the period between 1997 and 2011 to estimate the Okun's Law Coefficient, which captures the relationship between growth and employment. The analysis suggests that growth was not jobless. However, there is considerable variation across countries. Generally, the effect of growth on employment tends to magnify under more flexible hiring and firing rules. Yet even where labor markets are more tightly regulated, economic growth affects employment, not necessarily in the aggregate but in its composition. There is evidence that agricultural employment moves counter-cyclically, as opposed to non-agricultural employment. The effect is particularly pronounced in periods of economic crisis, suggesting that agriculture may serve as a shock-absorber for workers laid off in the industrial sector. Isolating non-agricultural employment reveals a stronger relationship between growth and job creation.